Different responses of extreme and mean precipitation to land use and land cover changes - Meng Zhang; Yanhong Gao; Jun Ge (npj Climate and Atmospheric Science)
Abstract Land use and land cover changes (LULCCs) can influence precipitation via changes in surface energy, water flux, and large-scale atmospheric circulation, with great implications for the sustainable development of nature and society. However, the impacts and mechanisms of these contributors to extreme precipitation changes compared with mean changes still need to be investigated. Here, we used the moisture budget equation to decompose precipitation changes into three primary contributing factors (evapotranspiration, atmospheric mean circulation, and water vapor) based on CMIP6-LUMIP experiments. A global reduction in mean precipitation due to LULCCs can be attributed to relatively equal contributions of changes in evapotranspiration and atmospheric mean circulation over the historical (1995–2014) and future (2080–2099) periods. In contrast, during the top drying month, the precipitation reduction is approximately 2–3 times greater than the multi-year mean change. The dynamic contributor representing the mean circulation change surpasses evapotranspiration as the primary contributor driving the extreme precipitation decrease in the majority of the landscape. The socioeconomic impacts of LULCCs-induced extreme precipitation changes are greater than those of the mean state, especially in the future.